Tema 2: Ethel and her Telenoid: Toward using humanoids to alleviate symptoms of dementia - Jens Dinesen Strandbech (Læring og Medier, 2015)
This article elaborates on a longitudinal study investigating if conversations with the teleoperated humanoid robot Telenoid can alleviate symptoms of dementia. The article initially frames Telenoid in the field of social robotics and relevant dementia-initiatives before dwelling on the emerging relationship between Telenoid and a person with severe dementia. Here it is shown how persons with severe dementia can benefit greatly from interaction with Functionally Designed Anthropomorphic Robots such as Telenoid as a means of providing a temporary ‘conversational stepping stone’, working toward improving quality of life and regaining conversational and social confidence to seek and interact socially with others.